ITRAQ-based quantitative proteomics analysis reveals the molecular mechanism of controlled atmosphere storage for Tibetan hull-less barley (Hordeum vulgare L) preservation. (November 2020) - Yang, Feiyan; Chen, Tao; Sun, Shuguo; Li, Beiping; Lin, Qinlu
Abstract: Controlled atmosphere storage (CAS) is an effective method for cereal grain preservation, but its mechanism is yet to be completely elucidated. In this study, the molecular mechanism of CAS was evaluated for Tibetan hull-less barley preservation using iTRAQ quantitative proteomics, Western blot, and physicochemical and individual volatiles analyses. In barley stored at 25 °C, compared with non-controlled atmosphere storage (NCAS), CAS altered the expression of 116 proteins by > 2.0 fold. Among these proteins, 82 downregulated proteins were mainly involved in carbon metabolism, protein and amino acid metabolism, and lipid and fatty acid degradation. Physicochemical analyses suggest that CAS could reduce the severity of abiotic stress. Bioinformatic and molecular biology analyses reveal that CAS could decrease the rates of carbon metabolism, protein and amino acid metabolism, and lipid and fatty acid degradation by downregulating some key proteins (Beta-amylase, 6-phosphofructokinase 1, isocitrate dehydrogenase, glutamate decarboxylase, 1-pyrroline-5-carboxylate dehydrogenase, seryl-tRNA synthetase, leucyl-tRNA synthetase, aspartyl-tRNA synthetase, aldehyde dehydrogenase (NAD+), and alcohol dehydrogenase), accompanied by significant reductions in oxidative dehydrogenation reactions ( p < 0.05). Together, a favorable environment provided by CAS ultimately mitigated physiological abnormalities, nutrient and energy consumption, and flavor deterioration in the barley. The proteomics analysis results were confirmed by Western blot, and physicochemical and individual volatiles analyses. Graphical abstract: Image 1 Highlights: Preservation mechanism of CAS for barley was evaluated using iTRAQ proteomics. CAS reduced rates of carbon and amino acid metabolism, and fatty acid degradation. CAS mitigated energy and nutrient consumption and the accumulation of off-flavor. Western blot, physicochemical and volatiles analyses confirmed proteomics results.